A educação como direito: a permanência como princípio na educação profissional integrada ao ensino médio - Kiessling, Hélio Fritz (2021)
This dissertation presents the results of a research whose object is the student's permanence in Technical Vocational Education of Middle Level (EPTNM) at the Federal Institute of São Paulo (IFSP), São Paulo campus. Permanence is seen as a result of the principle of equality of conditions to guarantee the right to education. The main objective is to verify how the permanence in the school has been treated in the legislation and other Brazilian regulations and serves as a basis for the elaboration of the norms and actions developed in the referred Institute, with a view to creating conditions for the students to remain in the EPTNM. This work covers public policies for the EPTNM and how it is implemented in the São Paulo campus of the IFSP. In the development of the research, we opted for a qualitative approach with an exploratory nature and, as a data collection instrument, a bibliographic survey and a documentary research of the federal legislation was used, together with its respective regulation through ministerial norms and others that guide the work of the researched institution with regard to the permanence of students in school. In addition to the Federal legislation and norms of the researched institution, a dialogue was carried out with authors whose works deal with the student's permanence in school (OLIVEIRA, 1999; CURY, 2002; 2008; MENESES; BATISTA, 2003; BOTO, 2005; DORE; LÜSCHER, 2011; LEITE, 2012; XIMENES, 2014; RAMOS, 2014; DAROS, 2015; OLIVEIRA; OLIVEIRA, 2015; LEITE, 2015; DUTRA; SANTOS, 2017; SANTOS, 2018; MATOS, 2018; ALMEIDA, 2019; SILVA; CARVALHO; GONÇALVES, 2021). The analysis of the collected data allows us to affirm that the permanence of students in school is fundamental to guarantee the right to Education and that its implementation has been a challenge for formulators and managers of educational policies in Brazil. In this context, the IFSP has developed actions aimed at creating conditions for the student's permanence in the Institution.